2017
DOI: 10.1111/den.12792
|View full text |Cite
|
Sign up to set email alerts
|

Considering the esophagogastric junction as a ‘zone’

Abstract: Siewert's classification of adenocarcinoma of the esophagogastric junction (EGJ) classifies tumors anatomically for determining the appropriate surgical technique. According to this classification, a type II tumor, true carcinoma of the cardia, is defined as a cancer within 1 cm proximal to 2 cm distal of the EGJ. Histological analysis indicates that the cardiac gland is present with a high degree of frequency between 1–2 cm to the gastric side and 1–2 cm to the esophageal side of the EGJ, which means that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Liu et al showed that the enhanced information obtained in the venous phase was more closely related to the invasiveness of GC (34). Therefore, the accurate depiction of the tumor in other phase images may be difficult, which in turn may affect the ROI delineation and ultimately affect the calculation of radiomic features (4). EGJ adenocarcinoma can be evaluated using ultrasound gastroscopy, contrast-enhanced CT, MRI, and PET/ CT.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al showed that the enhanced information obtained in the venous phase was more closely related to the invasiveness of GC (34). Therefore, the accurate depiction of the tumor in other phase images may be difficult, which in turn may affect the ROI delineation and ultimately affect the calculation of radiomic features (4). EGJ adenocarcinoma can be evaluated using ultrasound gastroscopy, contrast-enhanced CT, MRI, and PET/ CT.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, the stomach is composed of 3 regions, the cardia, fundus, and pylorus, each of which represents a unique type gland. The cardiac mucosa consists of foveolar, parietal, and chief cells [36]. The gastric gland, including the fundic gland in particular, can be subdivided into 3 parts, the isthmus, neck, and base of the gland.…”
Section: Discussionmentioning
confidence: 99%
“…Esophagogastric junction (EGJ) cancer is defined as cancer with an epicenter within 5 cm of the EGJ . An increasing number of reports have proposed that EGJ carcinoma should be considered separately from esophageal or gastric cancer for its specific clinicopathologic features and survival outcomes . In the West, while overall incidence of gastric cancer has decreased steadily, incidence of neoplasms located in EGJ has significantly increased in the past few decades, with an unfavorable prognosis even after curative resection …”
Section: Introductionmentioning
confidence: 99%